Предмет: Алгебра,
автор: Knowledge2233
Срочно нужна помощь в решении уравнения: (x^2 - 6x - 7)/x = (x^2 - 7)/x^2 - 6x - 7
Заранее, спасибо
Ответы
Автор ответа:
0
Попытка. Вдруг поможет.
x≠0 и x²-6x-7≠0
D=b²-4ac=36+28=64=8²
x1=(6+8)/2=7
x2=(6-8)/2=-1
x≠7 x≠-1
(x²-6x-7)²=(x²-7)×x
x⁴-6x³-7x²-6x³+36x²+42x-7x²+42x+49=x³-7x
x⁴-13x³+22x²+91x+49=0
x⁴+22x²+49-(13x³-91x)=0
x²=a
a²+22a+49-13x(x²-7)=0
Пробуем разложить на множители а²+22а+49
D=22²-4×49=484-196=288...
x≠0 и x²-6x-7≠0
D=b²-4ac=36+28=64=8²
x1=(6+8)/2=7
x2=(6-8)/2=-1
x≠7 x≠-1
(x²-6x-7)²=(x²-7)×x
x⁴-6x³-7x²-6x³+36x²+42x-7x²+42x+49=x³-7x
x⁴-13x³+22x²+91x+49=0
x⁴+22x²+49-(13x³-91x)=0
x²=a
a²+22a+49-13x(x²-7)=0
Пробуем разложить на множители а²+22а+49
D=22²-4×49=484-196=288...
Похожие вопросы
Предмет: Биология,
автор: mylnikovavarvara9
Предмет: Математика,
автор: smuzi14
Предмет: Литература,
автор: angelabramova11
Предмет: Литература,
автор: DEмастер59
Предмет: Биология,
автор: TOTI2001